2022
DOI: 10.4274/ejbh.galenos.2022.2022-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Tract Metastases of Invasive Lobular Carcinoma of the Breast: An Immunohistochemical Survey Algorithm

Abstract: The histopathological findings are similar in invasive lobular carcinoma of the breast and poorly cohesive carcinoma of the stomach. Therefore, the possibility of metastasis should be kept in mind in multiple erosions or linitis plastica type gastric lesions. •In breast cancer patients who develop gastrointestinal tract metastases, determining the nature of the tumor (primary or metastatic) is extremely important in terms of treatment. •The importance of histopathological examination is critical and is highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The diagnosis of BC was based on part of the biopsy tissue, not the surgical specimen. It is possible that the tumor originally had an ILC component based on the fact that ILC is able to metastasize to the gastrointestinal tract [ 9 ]. Interestingly, Mori et al reported a similar case in which BC was diagnosed as IDC and the appendix was diagnosed as ILC [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of BC was based on part of the biopsy tissue, not the surgical specimen. It is possible that the tumor originally had an ILC component based on the fact that ILC is able to metastasize to the gastrointestinal tract [ 9 ]. Interestingly, Mori et al reported a similar case in which BC was diagnosed as IDC and the appendix was diagnosed as ILC [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…[18] It is extremely rare for a patient with breast cancer to have both gastric and colonic metastases at the same time. Up to now, only ve case reports can be retrieved on PubMed and Web of Science [12,[19][20][21][22] , so we cannot obtain the speci c incidence rate.…”
Section: Discussionmentioning
confidence: 99%
“…Both Inoue and Zengel's case reports indicated positive expression of ER, GATA-3, CK7 and negative expression of CK20 in colonic metastases. [9,12] Horimoto presented a case of colonic polyp metastasis from breast cancer that was GCDFP-15 positive, CK7 positive and CK20…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations